Library@Orchard: an evaluation. - Chee, Veronica Hui Ling. (2008)
The study concluded that users generally had a good impression of the library and were satisfied with the services and facilities. However, none of the participants was aware of the full range of services and facilities available at Library@Orchard, a fact that has implications for marketing and customer service. An integral part of providing good service was the recommendation to employ staff who were knowledgeable about books. It was also recommended that a Children's Section be set up in a separate section of the library. Resources for other groups such as the elderly, younger teenagers, the handicapped and tourists were also discussed. Suggestions for facilitating access to collections included improving the selection of books, weeding the collection, the provision of attractive programming, the loan of videotapes, the provision of cashcard vending machines, and the provision of more OPACs.